IMPLEMENTASI PEMBANGUNAN KARAKTER DAN KREATIVITAS PEMBELAJARAN SISWA MELALUI PROGRAM UTAMA PADA SEKOLAH INDONESIA KUALA LUMPUR (SIKL) - Ainiya Nur Itsnaini; Dewi Anisatul Munawaroh; Sri Wahyuni Widyastuti; Nur Sholihah; Elya Umi Hanik (Program Studi Pendidikan Guru Sekolah Dasar, Fakultas Keguruan dan Ilmu Pendidikan Univers, 2021)
This research has the objective of describing the implementation of character development and student learning creativity through the main program at the Kuala Lumpur Indonesian School (SIKL). The methods or methods applied by researchers to this report are qualitative methods, namely techniques for collecting data sources from interviews and research journals which are prioritized on the theme of Implementation of Character Development and Student Learning Creativity. The results of research on the implementation of character building and student learning creativity through the main program at Sekolah Indonesia Kuala Lumpur (SIKL) are the existence of digital lesson plans, honesty canteen, SIKL TV channels, life-based curriculum, SIKL Expession Stage, learning at home